ASSESSMENT OF DIETARY AND LIFESTYLE FACTORS ASSOCIATED WITH DYSPEPSIA: A QUESTIONNAIRE-BASED STUDY - MAHESAR, M; BHUTTO, SA; BHATTI, WS; BHURGRI, GR; FATIMA, U; CHANDIO, M; MANGI, S; RANI, P; SANGI, K; CHANDIO, B; SHAIKH, M; ABBAS, W; et al. (Biological and Clinical Sciences Research Journal, 2024)
The main aim of this study was to better understand the connections between diet patterns and lifestyle choices and the development of dyspepsia providing useful insights into the impact of various dietary and lifestyle components on dyspeptic symptoms, contributing to the creation of focused interventions and recommendations for maintaining digestive health. Among the Pakistani general population, a cross-sectional study was carried out in November 2022. Demographic data, dietary lifestyle factors and frequency of dyspepsia were evaluated. An English-based questionnaire was distributed through Google form. A question related to assessing the dyspepsia frequency in participants and to examining lifestyle factors related to diet (various food consumption consisting of salty food, fast food or any beverages), alcohol consumption, smoking, use of (NSAIDS) medications and utilization of any other home remedies. The sample size of the participants was 351. An SPSS version 25 was used for data analysis. It was observed that 19% of participants were suffering from dyspepsia. Fast food, smoking, painkillers, salty food, and stress were associated with dyspepsia whereas H. pylori, consumption of alcohol and other factors are less likely responsible for dyspepsia. Dietary factors like beverages, tea/coffee, fruits/vegetables and physical activity indicate no significant relation with dyspepsia. It was observed through this study that 14% and 18 % of people were utilizing herbal medicines and home remedies for dyspepsia respectively. However, depression and inadequate sleep had a significant impact on dyspepsia. After a thorough examination of participant data, we were able to identify several significant correlations that offer important information about the possible causes of dyspeptic symptoms.